Gene expression, growth performance and body composition of Labeo rohita fingerlings fed on polyphenols supplement - Hussain, Syed Makhdoom; Jamil, Muniba; Ali, Shafaqat; Shahzad, Muhammad Mudassar; Hussain, Majid; Ahmad, Nisar; Riaz, Danish (Penerbit Universiti Kebangsaan Malaysia, 2023)
The aim of this research was to investigate the impacts of polyphenols-supplemented diet on growth, body composition and gene expressions of insulin-like growth factor (IGF) and growth hormone (GH) in Labeo rohita fingerlings fed canola meal-based diets. Two plant extracts; Salvadora persica and Salvadora oleoides were used to assess the efficacy of L. rohita. Twelve test diets, including control (no supplementation) and supplemented with S. persica, S. oleoides and their mixture at the levels of 200, 400 and 800 mg/kg, were formulated. The gene expression of IGFs and GH was observed to be regulated significantly (p< 0.05) in the liver tissue of fingerlings when fed with supplemented diet. The highest expression of GH was observed at 200 mg/kg mixture diet. The results of growth performance showed that maximum weight gain% (215%) and SGR (1.63) was recorded at 200 mg/kg mixture diet. The results of carcass analysis showed that they were significantly (p< 0.05) influenced by supplemented diet when compared with control diet. As growth performance is under genetic control, the synthesis and release of IGF are stimulated by binding of GH to receptors present in the liver. Conclusively, the results showed that rohu fingerlings shown the best results of growth performance, body composition and gene expression of IGF and GH, when fed on mixture of S. persica and S. oleoides at 200 mg/kg.